Peningkatan Kompetensi Guru dalam Membangun Budaya Literasi di Madrasah melalui Bimtek dengan Metode Bimbingan Langsung di MTsN 1 Siak Tahun Pelajaran 2023/2024 - Sakdiah Sakdiah (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
Literacy is very important for students because literacy skills will affect the success of their learning and their lives. Good literacy skills will help students understand oral, written and visual texts. oral, written, and pictorial/visual texts, therefore, the development of literacy in literacy in learning is always carried out in an integrated manner between listening, speaking, reading and writing activities. This is because the four skills have a very close relationship, although each has certain characteristics. One way that can be do to improve teacher competence in building a Literacy Culture in Madrasahs is through Technical Guidance with the Method of Direct Guidance. Bimtek is an activity that is intended to provide assistance which is generally in the form of advice and guidance and guidance to solve problems / problems that are technical in nature. From the results of research conducted on teachers at MTsN 1 Siak, namely as follows: Organizing Technical Guidance with the Direct Guidance Method can improve teacher competence in building a culture of Literacy in Madrasahs at MTsN 1 Siak in the 2023/2024 academic year. This This is indicated by the score of the observation of the teacher which continues to increase from cycle 1 to cycle 3. In cycle 1 the score obtained was 78, then increased in cycle 1 to cycle 3. obtained was 78, then increased in cycle 2 to 120, and the achievement of the maximum score of 144 occurred in cycle 1 to cycle 3. achievement of the maximum score of 144 occurred in cycle 3.